An overview of the policy-making role, functions and processes of the judiciary - Cabreros, Eduardo Q. Jr.
In the course of deciding legal questions, the judiciary makes policies and often gets to implement such policies too. In this article the author outlines the various policy-making mechanisms and processes governing the judiciary's power to make and execute policies as well as the effects and consequences of judicial policies
Keywords: Policy-Making; Philippine; Judiciary; Justice, Administration of - Philippines